A Case of Accessory Tragus on the Nasal Vestibule - Shin, Mi-Seon; Choi, Yeon-Jin; Lee, Jung-Yeon; Lee, See Hyun; Ahn, Ji-Young; Park, Mi-Youn; Park, Hyang-Joon (Annals of dermatology, 2010)
We present a case of accessory tragus (AT) which developed at an unusual site, the nasal vestibule, of a 1-day-old girl. To our knowledge, this is the first report of an accessory tragus that appears on the nasal vestibule.